Gegen die Diskussion mit den drei Unbekannten Daten, Algorithmen und Digitalisierung - Svenja Hagenhoff (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2020)
– The inflationary use of currently prominent terms, such as data centration or the digital age, without the effort of naming and explaining how the phenomena they refer to are to be understood and by which characteristics they are characterized, does nothing more than obscure meaning without any chance of gaining insight or well-founded opinion. Algorithms, data, digitization, and are three of the candidates that are frequently used but only rarely explained in a well-founded and differentiated manner. This article comes into this desideratum. It deals with these 'three unknowns' and attempts to grasp and substantiate the terms and the phenomena they refer to and to formulate what exactly is 'new' and what constitutes the quality of difference to previous states (age without digitization).
urn:nbn:de:bvb:29-opus4-150014
Keywords: 000; Algorithmisierung; Datafizierung; Datenzentrierte Geschäftsmodelle; Differenzqualität; Digitales Zeitalter